PERFECTION OF INVESTMENT ATTRACTIVENESS OF ALMATY - A.Т. Issayeva; , B.M. Iskakov; A.D. Nasyrkhanov (Academic Journal of Physical and Chemical Sciences, 2019)
Modern conditions of reproduction, increased competition among regions for resources have sharply increased the importance of the issues of investment support for the development of the regional economy. The problem of forming a mechanism of regional investment policy, increasing investment activity and attractiveness, improving the investment climate is one of the key issues in the field of regional economy and regional economic policy of the Republic of Kazakhstan. The authors note that the government of Kazakhstan pays considerable attention to investing in the regional economy, leveling out inter-regional differences, overcoming crisis phenomena and the backlog in the economic development of individual regions. The reasons for the investment attractiveness of Almaty are listed, problems arising on the path of improvement and methods for their solution are proposed.